Outcome of ventilation in patients with hypercapnic respiratory failure in IPF patients: A prospective study - Krishnappa, Manjunath Hunasenahalli; Thimmarayappa, Prasanna Kumar; Nangia, Vivek; Chatterji, Rajat (Asian Journal of Medical Sciences, 2021)
Background: Diffuse parenchymal lung disease (DPLD) is the inflammation and fibrosis of lung interstitium, resulting in respiratory failure. The rate of hypoxic respiratory failure is high as the disease progresses. In idiopathic pulmonary fibrosis (IPF) patients, acute deterioration leads to type 2 respiratory failure, etiology and management of which remains to be completely understood. Aims and Objectives: To identify the causes of type 2 respiratory failure and assess the outcome of invasive and non-invasive ventilation in patients with IPF. Materials and Methods: This prospective single center study included >18-year-old 44 patients with IPF. History of patients, complete blood count, chest radiograph, urine routine, spirometry with bronchodilator reversibility, DLCO (diffusing capacity for carbon monoxide) testing, arterial blood gas measurements, and antinuclear antibody (ANA) test were evaluated. Results: Fourteen (31.8%) patients developed type 2 respiratory failure (within 1.5–6 years from the time of onset of illness). Causes of respiratory failure included acute exacerbation of IPF (35.71%), infections (14.29%), heart failure (14.29%), ischemic heart disease (14.29%), pulmonary embolism (21.43%), pneumothorax (7.14%), and surgical lung biopsy (7.14%). Patients were initiated on non-invasive mechanical ventilation (NIV) (64.29%) and invasive mechanical ventilation (IMV) (35.71%). Eight (88.89%) out of 9 patients on NIV survived, whereas all 5 patients (100%) on IMV expired. Conclusion: Considering the higher mortality rate associated with IMV, NIV is a better technique than IMV for improving patient outcome and management. NIV may be effectively implemented for improving the treatment outcome in patients with IPF and avoiding any aggressive therapeutic approaches.